Cationic covalent organic framework for the fluorescent sensing and cooperative adsorption of perfluorooctanoic acid - Asmaa Jrad; Gobinda Das; Nour Alkhatib; Thirumurugan Prakasam; Farah Benyettou; Sabu Varghese; Felipe Gándara; Mark Olson; Serdal Kirmizialtin; Ali Trabolsi (Nature Communications)
Abstract The contamination of water by per- and polyfluorinated substances (PFAS) is a pressing global issue due to their harmful effects on health and the environment. This study explores a cationic covalent organic framework (COF), TG-PD COF, for the efficient detection and removal of perfluorooctanoic acid (PFOA) from water. Synthesized via a simple sonochemical method, TG-PD COF shows remarkable selectivity and sensitivity to PFOA, with a detection limit as low as 1.8 µg·L⁻¹. It achieves significant PFOA adsorption exceeding 2600 mg·g⁻¹ within seconds over several cycles in batch mode and complete removal at environmentally relevant concentrations in column adsorption. Results reveal unique adsorption behavior characterized by two phases, leveraging PFOA aggregation through hydrophobic interactions. Computer simulations elucidate the mechanisms underlying TG-PD COF’s sensing, adsorption, and charge transfer dynamics. Our findings position this COF design strategy as a promising solution for combating PFAS contamination in water bodies worldwide.